Hubungan Berat Badan Lahir Rendah Dengan Kematian Neonatal di Kabupaten Bangkalan - Ananda, Devi Fitria; Afridah, Wiwik (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research examines the relationship between low birth weight and neonatal mortality in Bangkalan Regency. Low birth weight (LBW) is a major factor in the increased mortality, morbidity and disability of newborns, infants and children and has a long-term impact on their future life. The purpose of this study was to determine the relationship between low birth weight (LBW) and neonatal mortality in Bangkalan Regency in 2021. This type of research is non-reactive with an ecological study research design with a cross sectional approach. The population and samples in this study were 22 Puskesmas in Bangkalan Regency and recorded in the Maternal and Child Health Local Area Monitoring Report (PWS KIA) of the Bangkalan District Health Office in 2021. The variables studied were LBW and neonatal mortality. Data analysis using the Spearman test. The results showed that the prevalence of low birth weight cases that occurred was (0.3%), and for the prevalence of neonatal deaths was (0.8%). There is a relationship between LBW and neonatal mortality (Sig < 0.1, correlation coefficient 0.437). The conclusion of this study there is a relationship between low birth weight and neonatal mortality in Bangkalan Regency in 2021. Suggestions for Puskesmas to improve communication to pregnant women so that pregnant women get clear benefits about the benefits of consuming TTD or provide recommendations for blood supplement tablets other than those obtained from puskesmas if they may not be suitable for pregnant women's conditions with the supervision of health workers.